Perceptions of Nigerian Women about Human Papilloma Virus, Cervical Cancer, and HPV Vaccine - Olusola Anuoluwapo Akanbi; Abiodun Iyanda; Folakemi Osundare; Oluyinka Oladele Opaleye (Scientifica)
Background. Cervical cancer caused by human papilloma virus (HPV) though preventable has claimed the lives of many women worldwide. This study was embarked upon to evaluate the general knowledge and perceptions of Nigerian women on HPV, cervical cancer, and HPV vaccine. Methods. Structured questionnaires were administered to a cross section of 737 women randomly selected from the general population in two southwestern States of Nigeria. Statistical analysis was done using SPSS computer software version 16. A P value >0.05 was considered statistically significant. Results. One hundred and seventy-six (23.9%) of the respondents had knowledge of HPV; 474 (64.3%) are aware of cervical cancer but only 136 (18.5%) know that HPV causes cervical cancer. 200 (27.1%) are aware that there is an HPV vaccine while 300 (40.7%) had knowledge of Pap smear test. Two hundred and sixty (35.3%) of the respondents know that early detection of HPV can prevent cervical cancer and in spite of this, only 110 (14.9%) have taken the Pap smear test before while 151 (20.5%) are not willing to go for the test at all. Conclusions. There is therefore the need to create proper awareness on the HPV and its possible consequence of cervical carcinoma.